Risk of Revocation Among Batterers: A Preliminary Analysis of Criminogenic, Intimate Partner Violence, and Mental Health Risks - Garner, Alisa R. (Violence against women, 2021)
This study examined whether criminogenic risk, domestic violence risk, and mental health diagnoses would predict probation revocation among batterers in a felony domestic violence court (FDVC). Review of probation files included baseline assessments and probation disposition for FDVC probationers from January 2014 to March 2018 (n = 64). Results of the binary logistic regression analysis showed that criminogenic risk was a significant predictor of FDVC probation revocation. Interventions to prevent unsuccessful completion of domestic violence courts may benefit from programming that addresses early engagement in treatment, antisocial thinking patterns, and treatment for substance use disorders.